2021
DOI: 10.3389/fpsyg.2021.545268
|View full text |Cite
|
Sign up to set email alerts
|

Beholden: The Emotional Effects of Having Eye Contact While Breaking Social Norms

Abstract: This study looks into the role that eye contact plays in helping people to control themselves in social settings and to avoid breaking social norms. Based on previous research, it is likely that eye contact increases prosocial behavior via heightened self-awareness and increased interpersonal synchrony. In our study, we propose that eye contact can also support constructive social behavior by causing people to experience heightened embarrassment when they are breaking social norms. We tested this in a lab expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…Additionally, when comparing E-A and E-NA, E-NA's VA seems to be preferred (see Figure 6 (a)) and more effective than E-A's VA (see Table 2 (b)). This may be aligned with a prior study [68] that negative emotional behavior with eye contact can worsen negative effects. Such behaviors were included in E-A's features but should be further explored.…”
Section: The Specific Types Of Vas That Affect User's Decisionssupporting
confidence: 89%
“…Additionally, when comparing E-A and E-NA, E-NA's VA seems to be preferred (see Figure 6 (a)) and more effective than E-A's VA (see Table 2 (b)). This may be aligned with a prior study [68] that negative emotional behavior with eye contact can worsen negative effects. Such behaviors were included in E-A's features but should be further explored.…”
Section: The Specific Types Of Vas That Affect User's Decisionssupporting
confidence: 89%
“…Human evolution has favored communicative eyes [ 61 ]. For example, in the study of Singh et al [ 62 ], having eye contact during norm-breaking behavior as compared to no eye contact led to a stronger increase in self-reported embarrassment, a higher heart rate, more hesitation and laughter. They concluded that eye contact gives people the power to punish norm breaking in others by inducing an aversive emotional experience.…”
Section: Discussionmentioning
confidence: 99%